Effects of hydrogen addition on nanostructure and reactivity of carbon particles in flame–wall interactions. Issue 11 (2nd November 2018) - Luo, Minye; Liu, Dong
Abstract: An experimental study was performed to investigate the influence of hydrogen addition on carbon particles (soot) characteristics in flame–wall interactions through the ethylene jet diffusion impinging flames. Different soot rings were formed on the plate surface when the impinging flames propagated along the plate surface. The nanostructure, oxidation reactivity and other internal properties of inner and outer ring soot were comparably analyzed with the help of high-resolution transmission electron spectroscopy (HRTEM), thermogravimetric analyzer (TGA) and X-ray diffraction (XRD). The results showed that the inner ring soot was the liquid-like material with the amorphous structure. The outer ring soot was composed of primary spherical particles with classic core-shell structures. The increasing addition of hydrogen promoted the disordered extent of inner ring soot with the decrease of fringe length and the increase of fringe tortuosity. It was potentially attributed to the reduction of nucleation rates and the less condensation of PAHs on the particle surface. The degree of graphitization for outer ring soot increased and the opposite trends of fringe length and tortuosity variations were observed when part of ethylene was substituted by hydrogen. It might be due to the higher flame temperature of the post-impingement region which led by the decrease of flame domain contacted to the plate and the enhancement of soot oxidation by increased OH radicals. The oxidation reactivity increased for the inner ring soot and decreased for the outer ring soot with the increasing addition of hydrogen. It also verified the correlation between soot nanostructure and oxidation reactivity that soot with the higher graphitization degree of nanostructure presented the lower oxidation reactivity.